LKPD-BASED LEARNING TO IMPROVE SCIENCE LEARNING OUTCOMES OF GRADE IV SD/MI STUDENTS - IDAYANTI, ZULFI; SULEMAN, MUH. ASHARIF; SUHARDI, MUHAMAD (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2024)
This study aims to determine whether LKPD-based learning can improve science learning outcomes for grade IV. This type of research is Classroom Action Research (CAR) using the Kemmis and Taggart model, with the research subjects being 25 grade IV students of SD Negeri Demangan and 1 class teacher. This research was conducted in 2 cycles consisting of planning, implementation, observation, and reflection. The research instruments consisted of observation sheets, learning devices, student worksheets (LKPD), post-test question grids, and post-test question sheets. Data collection methods consisted of tests at the end of each cycle and non-tests consisting of observation, interviews, and documentation. Technical data analysis consisted of qualitative data analysis on how students and teachers' activities were and quantitative analysis on the learning outcomes achieved by students at the end of each cycle. The indicators of success in this study were: (1) obtaining a score ? KKM, which was 71; (2) achieving classical completeness if 85% of the total number of students obtained a score ? KKM, which was 71. Student activity during learning has increased, from an average of 73% in cycle 1 with a high category to 89% in cycle 2 with a very high category. Student learning outcomes show an average value of learning outcomes in cycle 1 of 71.7, and in cycle 2 it has increased to 84.5. The increase in the average value of student learning outcomes has exceeded the KKM value set by the school, which is 71. The classical percentage of student learning completion in the pre-cycle was 36%; in cycle 1, it increased to 67%; and in cycle 2, it reached 88%. The classical completion of students who reached 88% in cycle 2 has exceeded the minimum completion criteria set, which is 85%. This means that LKPD-based learning can improve the science learning outcomes of grade IV students of SD Negeri Demangan. ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah pembelajaran berbasis LKPD dapat meningkatkan hasil belajar IPA siswa kelas IV. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) dengan menggunakan model Kemmis dan Taggart, dengan subjek penelitian sebanyak 25 siswa kelas IV SD Negeri Demangan dan 1 guru kelas. Penelitian ini dilakukan dalam 2 siklus yang terdiri atas perencanaan, pelaksanaan, observasi, dan refleksi. Instrumen penelitian meliputi lembar observasi, perangkat pembelajaran, Lembar Kerja Peserta Didik (LKPD), kisi-kisi soal post-test, dan lembar soal post-test. Metode pengumpulan data terdiri atas tes pada akhir setiap siklus dan non-tes berupa observasi, wawancara, serta dokumentasi. Teknik analisis data meliputi analisis data kualitatif terhadap aktivitas siswa dan guru serta analisis kuantitatif terhadap hasil belajar siswa di akhir setiap siklus. Indikator keberhasilan dalam penelitian ini adalah: (1) memperoleh nilai ? KKM, yaitu 71; (2) mencapai ketuntasan klasikal apabila 85% dari jumlah siswa memperoleh nilai ? KKM. Aktivitas siswa selama pembelajaran meningkat, dari rata-rata 73% pada siklus 1 (kategori tinggi) menjadi 89% pada siklus 2 (kategori sangat tinggi). Hasil belajar siswa menunjukkan rata-rata nilai hasil belajar pada siklus 1 sebesar 71,7, yang meningkat menjadi 84,5 pada siklus 2. Peningkatan rata-rata nilai hasil belajar siswa telah melampaui nilai KKM yang ditetapkan sekolah, yaitu 71. Persentase ketuntasan belajar klasikal siswa pada pra-siklus adalah 36%; pada siklus 1 meningkat menjadi 67%; dan pada siklus 2 mencapai 88%. Ketuntasan klasikal siswa sebesar 88% pada siklus 2 telah melampaui kriteria ketuntasan minimum yang ditetapkan, yaitu 85%. Hal ini menunjukkan bahwa pembelajaran berbasis LKPD dapat meningkatkan hasil belajar IPA siswa kelas IV SD Negeri Demangan.